The science behind marine-oil snow and MOSSFA: Past, present, and future. (August 2020) - Burd, Adrian B.; Chanton, Jeffrey P.; Daly, Kendra L.; Gilbert, Sherryl; Passow, Uta; Quigg, Antonietta
Highlights: A review of the science behind the formation and fate of marine-oil-snow. An identification of important future directions for research. A synthesis of evidence for the importance of marine-oil-snow and MOSSDFA. Abstract: The 2010 Deepwater Horizon oil spill in the Gulf of Mexico demonstrated that oil in the water column may be transported from surface waters to the sediments via marine snow. Interactions between oil droplets and mineral particles have been intensively studied since the middle of the twentieth century, but interactions between oil and organic particles, such as phytoplankton, fecal pellets, and other organic detritus, have had less attention, and the formation of bacterial-oil aggregations has been unrecognized until now. Much has been learned about marine oil snow (MOS) sedimentation and flocculent accumulation (MOSSFA) since the Deepwater Horizon blowout. This review brings together this new understanding and highlights important areas where further investigation is needed.